2016
DOI: 10.5486/pmd.2016.7563
|View full text |Cite
|
Sign up to set email alerts
|

Pexiderization of some logarithmic functional equations

Abstract: We study some new logarithmic functional equations and their Pexiderizations on different structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…2. If 𝐴 = 𝔽 + , where 𝔽 is an ordered field then the general solution of equation ( 1) are also the constant functions (Glavosits et al, 2016). The proof requires only one substitution.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…2. If 𝐴 = 𝔽 + , where 𝔽 is an ordered field then the general solution of equation ( 1) are also the constant functions (Glavosits et al, 2016). The proof requires only one substitution.…”
Section: Discussionmentioning
confidence: 96%
“…In (Glavosits et al, 2016) we have shown that if 𝔽(+,⋅, ≤ ) is an ordered field, 𝑌 is an arbitrary nonempty set, then the functional equation ( 1) has only constant function solutions on 𝔽 + . In (Glavosits et al, 2016) equation ( 1) is necessary to show that a Pexider type functional equation has only quasi logarithmic function solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could perhaps be improved writing simply ordered field instead of Archimedean ordered field, that is, The above two problems have probability background see [18], [2], [13], and [11]. Two pairs of new equations can be derived from the above two equations, the Pexider versions of the second of these equations (which contain the unknown gamma function) characterize the logarithmic functions see [12].…”
Section: Additional Applications and Conjecturesmentioning
confidence: 99%
“…In papers (Davison, 2001;Davison, 1974a;Davison, 1974b; Davison and Redlin, 1980) the equation (1.1) was investigated on various abstract structures. In paper (Fenyő, 1970) a Pexider version (that is functional equation with more unknown function [Aczél, 1983;Aczél and Dhombres, 1989;Kuczma, 1985;Glavosits and Lajkó, 2016]) of equation (1.1) and its locally integrable function solutions can be found. See also (Lajkó et al, 2009;Lajkó and Mészáros, 2015).…”
Section: Introductionmentioning
confidence: 99%